Fraud in criminal law: a normative and criminological analysis of fraudulent crime in Croatia and the regional context - Sokanović, Lucija (Research Series of the Max Planck Institute for Foreign and International Criminal Law Publications of the Max Planck Partner Group for Balkan Criminology, 2019)
New forms of criminal fraud are constantly emerging and their incidence is increasing. This book provides in-depth analyses of whether, and how exactly, criminal law perceives and adapts to these developments. The main focus of the study are the relevant normative and criminological questions regarding fraud, fraud in economic transactions, subsidy fraud, computer and electoral fraud, and some other forms of fraudulent behaviour. From a comparative perspective, it becomes apparent that a specific group of statutory offences is scattered throughout the criminal codes of Croatia, Germany, Austria and Switzerland and also the neighbouring countries in the Balkan region, all of which fit the same pattern and reveal the same core features of fraud. Criminal law addresses them in the same manner, hence a “fraud-related criminal law” can be identified. This should be of help for developing and applying adequate measures for effective detection and prosecution of this type of offences. Standardization of legal protection against fraud is reflected upon as an instrument that represents the dynamics of the transition and integration of European countries and the globalization of the economy, with their growing intensity of economic cross-border transactions.